Recent advances in screening of enzymes inhibitors based on capillary electrophoresis - Mengxia Cheng; Zilin Chen (Elsevier, 2018)
Capillary electrophoresis with many advantages plays an important role in pharmaceutical analysis and drug screening. This review gives an overview on the recent advances in the developments and applications of capillary electrophoresis in the field of enzyme inhibitor screening. The period covers 2013 to 2017. Both the pre-capillary enzyme assays and in-capillary enzyme assays which include electrophoretically mediated microanalysis (EMMA) and immobilized enzyme microreactor (IMER) are summarized in this article. Keywords: Capillary electrophoresis, Enzyme inhibitor screening, Pre-capillary enzyme assays, Electrophoretically mediated microanalysis, Immobilized enzyme microreactor